PRODUCTION OF L-TRYPTOPHAN BY MUTANTS OF CORYNEBACTERIUM GLUTAMICUM - Hamies Mohamed; Ghada El Nady; A. Ali; A. Abdel-Razik; S. Ibrahim (Arab Universities Journal of Agricultural Sciences, 2018)
L-Tryptophan, is one of the amino acids, also is one of the 9 essential amino acids of human which cannot be synthesized internally by him, microbial production is the main method for obtaining tryptophan for commercial uses. Typical microorganisms used for tryptophan production are E. coli and C. glutamicum. In this study, random mutations is performed on two strains of C. glutamicum to increase tryptophan production, the produced tryptophan measured by bioassay using tryptophan auxotroph E. coli (JW1254-2) strain, the mutations are performed using UV radiation. To detect and compare the difference between the parent strains and the muted strains genetically two molecular markers were used start codon targeted polymorphism (SCoT) and Inter-simple sequence repeats (ISSR). Tryptophan remarkably increased after C. glutamicum mutation to reach 278.4 µg/ml (1257.4% increment) from one mutated strain. Molecular genetics methods showed an ability to distinguish between the two original strains and their mutants and it showed the importance of the mutation by UV radiation for increasing the productivity of the bacteria to tryptophan.